2011
DOI: 10.1177/0961203311405703
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency and its association with disease activity in new cases of systemic lupus erythematosus

Abstract: Evidence has shown a relationship between vitamin D deficiency and systemic lupus erythematosus (SLE). We evaluated the frequency of vitamin D deficiency and its association with disease activity in new cases of SLE. Women with newly diagnosed SLE, based on the American College of Rheumatology (ACR) criteria, were enrolled consecutively. Those receiving vitamin D supplements and postmenopausal women were not included. Disease activity was measured by the BILAG index (2004) and serum concentration of 25-hydroxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
65
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 18 publications
11
65
0
2
Order By: Relevance
“…42 On these basis 1.25(OH)D appears able to regular and probably to contain autoimmune pathological mechanisms. In particular, as regards systemic lupus erythematosus, several studies have confirmed a relationship between low 25(OH)D levels and enhanced disease activity, 21 however, to date there is no high-level evidence to support that vitamin D supplementation may prevent or influence this disease. Other studies were carried out on possible influence of vitamin D status on rheumatoid arthritis without finding any relationship between 25(OH)D and levels of rheumatoid factor or anti-cyclic citrullinated peptide antibodies, 43 whereas an increased incidence in deficiency was found only in undifferentiated arthritis.…”
Section: Immunomodulation Effectmentioning
confidence: 99%
See 2 more Smart Citations
“…42 On these basis 1.25(OH)D appears able to regular and probably to contain autoimmune pathological mechanisms. In particular, as regards systemic lupus erythematosus, several studies have confirmed a relationship between low 25(OH)D levels and enhanced disease activity, 21 however, to date there is no high-level evidence to support that vitamin D supplementation may prevent or influence this disease. Other studies were carried out on possible influence of vitamin D status on rheumatoid arthritis without finding any relationship between 25(OH)D and levels of rheumatoid factor or anti-cyclic citrullinated peptide antibodies, 43 whereas an increased incidence in deficiency was found only in undifferentiated arthritis.…”
Section: Immunomodulation Effectmentioning
confidence: 99%
“…Immune system Hypovitaminosis D inhibits maturation of monocyte-derived dendritic cells 20 Low 25(OH)D levels are associated with SLE 21 Oncological diseases 25(OH)D reduces aromatase expression reducing breast cancer growth 22 Low 25(OH)D is associated with high incidence of cancers of colon, 23 breast and prostate 24 High dosage (1000 IU/d) of vitamin D can reduce the risk for total cancer 25 BMD, bone mineral density; SLE, systemic lupus erythematosus. of type 2 diabetes mellitus, hypertension, hyperlipidemia, and peripheral vascular disease, coronary artery disease, myocardial infarction, heart failure, and stroke.…”
Section: Potential Role Of Vitamin D In Older Peoplementioning
confidence: 99%
See 1 more Smart Citation
“…Although studies of 25-hydroxyvitamin D [25-(OH)D] levels and disease activity in patients with SLE have not had consistent results, most cross-sectional studies show an inverse relationship between the levels of vitamin D and disease activity. [6][7][8][9][10][11][12] Although the association between disease activity and serum levels of 25-(OH)D has been demonstrated in adults, considerably less is known about this relationship in children with SLE. The aims of this study were to evaluate the vitamin D status in pediatric patients with SLE and to examine whether there is an association between the serum levels of 25-(OH)D and disease activity in this autoimmune disease.…”
mentioning
confidence: 99%
“…Apart from its main function, which is calcium and bone metabolism, vitamin D is also necessary for the normal function of other organs and systems [4][5][6]. Calcitriol acts on target cells by binding to a nuclear receptor VDR (vitamin D receptor).…”
Section: Introductionmentioning
confidence: 99%